2020
DOI: 10.4103/sajc.sajc_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative CA-125 cutoff value and percent reduction in CA-125 levels correlate with surgical and survival outcome after neoadjuvant chemotherapy in patients with advanced-stage ovarian cancer? – Our experience from a tertiary cancer institute

Abstract: Aim: The aim of the study is to evaluate percent fall in CA-125 levels after neoadjuvant chemotherapy (NAC) and preoperative CA-125 value to predict surgical and survival outcomes in women with advanced-stage epithelial ovarian cancer (EOC). Methods: A retrospective review of 406 women receiving NAC for advanced-stage EOC from January 2012 to July 2015 was conducted. Data were collected for demography, radiographic profile, CA-125 levels before and after NAC, chemotherapy, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 13 publications
(17 reference statements)
0
15
2
Order By: Relevance
“…The QUIPS quality assessment outcomes of the included studies are reported in Supporting Information Supplementary Table S3 . Generally, the risk of bias was low for most studies [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The risk of bias was moderate for only three studies [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The QUIPS quality assessment outcomes of the included studies are reported in Supporting Information Supplementary Table S3 . Generally, the risk of bias was low for most studies [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The risk of bias was moderate for only three studies [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were prospective cohort studies [ 15 , 25 ]; the other twelve studies were retrospective cohort studies [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 ]. Four out of 14 studies reported the results of patients who underwent primary CRS [ 15 , 16 , 17 , 25 ], and nine studies reported the results of patients who underwent interval CRS [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 ]. One study reported patients undergoing either primary or interval CRS [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study published by Gupta et al . 26 showed that a 95% reduction of CA-125 levels and an absolute preoperative CA-125 level of 100 IU/ml or less predicted complete gross resection after NACT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results showed that the interval between preoperative and postoperative chemotherapy was significantly correlated with both PFS and OS; we established the threshold of 35.5 days by ROC curve analysis, such that patients with an interval between preoperative and postoperative chemotherapy of < 35.5 days had better PFS and OS, yielding an improvement in PFS and OS of 5.6 months and 25.4 month, respectively. In addition, regarding the decline in CA125 levels after NACT, a published study reported that a CA125 decrease of > 95% after NACT and CA125 level < 100 U/ml before IDS were related to better surgical outcomes and prognosis [ 23 ]. Similarly, we concluded that a normal CA125 level before IDS was associated with better OS and PFS, but in our study, a > 90% decrease in CA125 levels after NACT did not correlate significantly with optimal cytoreduction or prognosis.…”
Section: Discussionmentioning
confidence: 99%